Research on Chemistry Teaching Skills in Middle School Under Micro-Teaching Environment - Wang, Chenyu; Jia, Tianmeng; Sun, Lin (Advances in Social Sciences Research Journal, 2023)
Teaching skills are the foundation of teacher’s ability, and normal students, as the reserve army of future teachers, should train teaching skills consciously in their daily life. As a modern teaching technique widely used in training normal students, micro-teaching is of great significance to explore the cultivation of teaching skills. It should be widely introduced into the training of normal university students. However, there are relatively few researches on teaching skills in micro-teaching of chemistry at present, so we devote to studying the key skills that normal students should master in micro-teaching and the training methods of chemistry teaching skills under micro-teaching environment.This paper will use the practical cases in Chinese middle school chemistry teaching to help normal university students majoring in chemistry to master four key teaching skills: import skills, questioning skills , blackboard writing skills and reinforcement skills, so as to help them achieve the ideal teaching effect.